The effects of large negative intrathoracic pressure on left ventricular function in patients with coronary artery disease - Scharf, S M; Bianco, J A; Tow, D E; Brown, R (Circulation (New York, N.Y.), 1981)
Using first-pass radionuclide ventriculography, we evaluated the effects of decreases in intrathoracic pressure (Mueller maneuver [M] to -20 to -30 cm H2O) in 14 patients with five patients without coronary artery disease (CAD) and in 12 normal control subjects. In the patients with CAD, control ejection fraction was 0.53 +/- 0.06 (SEM) and control heart rate was 83 +/- 6 beats/min. These did not change during M. In the patients with CAD, control ejection fraction was 0.37 +/- 0.03 and heart rate was 82 +/- 7 beats/min. During M, heart rate did not change, but ejection fraction decreased to 0.33 +/- 0.33 (p less than 0.01). Examination of regional wall motion abnormalities showed akinesis of at least one myocardial segment in nine of 14 patients with CAD, but in none of the patients without CAD, nor in any of the 12 previously studied normal subjects (retrospectively analyzed). These data are consistent with the hypothesis that the Mueller maneuver acts to increase afterload placed on the left ventricle. Furthermore, in patients with CAD, the Mueller maneuver may have induced localized myocardial ischemia or unmasked areas of preexisting marginal function.